Performance Management As a Mediation of Variable of Competence and Coaching Skills That Impacts Organization Sustainability - Primadi Candra Susanto; Ni Nyoman Sawitri; Hapzi Ali; Sugeng Suroso; Istianingsih Sastrodiharjo (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to analyze the variables of competence with performance management, competence with organization sustainability, coaching with performance management, coaching with organizational sustainability, and performance management with organizational sustainability. The research method used is qualitative by reviewing the literature related to the variables in this study. The results of the study that of all references to variables stated have a direct influence from the reference to the article displayed, it's just that there are two variables that are not Fulfilled by not finding scientific articles related to the variables in this study. The gaps of this study are servant leadership variables, gender implication, intervention in organization, effectiveness, mechanism, employee performance, intrinsic motivation, work commitment, organizational citizens behavior, organizational effectiveness, and quality management.